Perbandingan Metode Bishop dan Janbu dalam Analisis Stabilitas Lereng pada Oprit Jembatan Labu Sawo Sumbawa - Dedy Dharmawansyah; Hermansyah Hermansyah; Nasrul Amri (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2021)
Abstract The oprit pile of Labu Sawo Bridge has a height of about 9.70 m with a length of 125 m, planning the labu sawo bridge oprit there is a problem in the subgrade is a type of clay soil which is not good because it has low soil bearing capacity, high moisture content and cracks (DPT) due to landslides so that they have the potential to experience ground movement and shifting. Therefore, calculation of slope stability and soil bearing capacity needs to be done to determine how much the slope safety and bearing capacity of the embankment soil. In the calculation of the analysis, the method used to find the safety value (SF) of the embankment slope is the Bishop and Janbu method. From the results of the method used, the security number given is calculated and then the safety figure is calculated. Based on the calculation results, the oprite embankment slope is categorized as a stable slope with the safety value of the Bishop method of 1.262. while the slope stability analysis used the Janbu method of 1.455 from the Bishop and Janbu method, the oprite slope of the Labu Sawo Bridge was categorized as slope in stable condition. Keywords : Slope stability, Bishop, Jambu.